A Clean, Sustainable and Stability-Indicating Method for the Quantification of Ceftriaxone Sodium in Pharmaceutical Product by HPLC. (15th June 2021) - da Trindade, Mariana Teixeira; Kogawa, Ana Carolina; Salgado, Hérida Regina Nunes
Abstract: Ceftriaxone sodium is a widely used antimicrobial, which is only available as a lyophilized powder. The presence of methods for evaluating the quality of this product is very important and helps to ensure its effectiveness, in addition to contributing to the fight against bacterial resistance. Therefore, a clean and sustainable high-performance liquid chromatography (HPLC) method has been developed for evaluating ceftriaxone stability in pharmaceutical product. A Zorbax SB C18 (150 × 4.6 mm, 5 μm) column was maintained at 25°C; the mobile phase consisted of purified water acidified with 0.2% orthophosphoric acid and ethanol (87: 13, v/v) at a flow rate of 0.9 mL min −1 . The detection wavelength was set at 260 nm. The method was linear over a concentration range of 20–120 μg mL −1, precise with relative standard deviations <2%, robust in the event of minor changes to the original method conditions, accurate with recovery between 98% and 102% and specific to degradation products. The retention time for ceftriaxone sodium was ~4.6 minutes. This work shows an ecologically correct option by HPLC method for the evaluation of ceftriaxone sodium in pharmaceutical product, as well as its stability, which addresses the requirements of the current green and sustainable analytical chemistry.